Effects of Annealing Temperature on Thermomechanical Properties of Cu-Al-Ni Shape Memory Alloys - Canbay, C. Aksu; Karagoz, Z. (Springer/Plenum Publishers, 2013)
The effects of the annealing temperature on structural properties and the phase transformation of a Cu-14.1Al-3.9Ni (mass %) shape memory alloy (SMA) have been investigated. The annealing process was carried out at temperatures in the range of to . The structural changes of the as-quenched and annealed samples were studied by optical microscope and X-ray diffraction measurements. The evolution of the transformation temperatures was studied by differential scanning calorimetry with different heating and cooling rates. The activation energy and thermodynamic parameters of the samples were determined. It was found that the heat treatment has an effect on the characteristic transformation temperatures and on thermodynamic parameters such as enthalpy, entropy, and activation energy. The crystallite size of the as-quenched and annealed samples were determined. Vickers hardness measurements of the as-quenched and annealed samples were also carried out. It is evaluated that the transformation parameters of a CuAlNi SMA can be controlled by heat treatment.
Keywords: Austenitic transformation; Martensitic transformation; Microstructure; Shape memory alloy